Evaluación técnico-financiera del uso de aditivos a base de nanotecnología para la mejora del rendimiento en un fluido de perforación base agua a nivel laboratorio (2019)
In this project the use of three additives based on nanotechnology within the formulation of a drilling fluid is evaluated; These additives are a nano filtering controller, a nano lubricant and finally a nano viscosifier. The performance of these additives is evaluated by comparing the results obtained from the laboratory tests with the results of the conventional additives used in the formulation of a base fluid. The development of the project is based on 5 phases to solve the proposed objectives. The first phase consists of a compilation of information about the laboratory tests performed on the drilling fluid. Additionally, the information concerning conventional additives and nano additives is presented along with the introduction to nanotechnology. The second phase comprises the formulations of the fluids to be evaluated with the different concentrations in order to determine the formulation based on nanotechnology that presents higher performance with respect to the base fluid formulated with conventional chemical additives. The third phase consists in carrying out each of the formulations described in phase two and performing the laboratory tests to determine the physical and chemical properties of the fluid; properties that are determined by performing API density tests, API filtering, HPHT, PPT, chemical tests (Mf, Pf, chlorides & calcium), rheology and swell meter. The fourth phase is the phase of analysis of the results of the tests carried out in phase three, where the formulations of the fluids based on nanotechnology are chosen that showed higher performance compared to the formulation of the base fluid. The fifth and final phase is the phase of the financial analysis of the project, where the viability of the implementation of the nanotechnology-based additives is determined through the use of the financial indicator VPN, with which the cost analysis is obtained and with it the culmination of the project.